How cognitive diversity in senior management teams can add value through innovation and improved performance in the mining industry. - Houston, Sam (Cranfield University, 2021)
The mining industry has a reputation for being insular, traditional, highly technical and macho and is not adapting quickly enough to meet the demands of a world that is changing at an ever-increasing rate. Key disruptions in the mining industry are in technology, legislation, sustainability requirements and stakeholder expectations. This dissertation proposes that rebalancing cognitive diversity in mining’s senior management teams will establish the industry’s ability to proactively manage disruptive events and that the industry needs to change the way it designs and manages individuals, teams and organisations from a diversity perspective. These two research aims were met though analysing results from a literature review, and surveys and interviews of senior leaders from the mining industry. A key finding from this research is that the industry is correcting its demographic imbalances although progress is slow and in reaction to social equality movements and legislation, rather than being proactive. Proactively managed cognitive diversity in senior management teams has been found to improve innovation and performance and there is an appetite for change regarding diversity and inclusion from senior leaders within the mining industry, although there is low awareness of cognitive diversity and its value. The conclusion from this research is that to be effective at mitigating its largest risks and issues, the industry needs to leverage cognitive diversity within senior management teams. However, leaders currently do not have access to toolkits to be able leverage cognitive diversity and the mining industry lacks psychological safety and relatedness to allow diversity to be leveraged. The key recommendations from this research were that more research is needed regarding how cognitive diversity can be leveraged within the mining industry, senior management teams in mining need to be more cognitively diverse, and leaders need a toolkit to help them to be successful in managing cognitive diversity.
Keywords: Diversity in the workplace; diversity; cognitive diversity; inclusion; equality; equity; mining industry; extraction industry; resource extraction; mines and mineral resources; leadership; senior management; executives; board of directors; corporate culture; cognitive bias; intuition; change theory; teams in the workplace; work environment; employee selection; management; creativity; innovation; job performance; orgainzational development; personnel recruitment; gender differences; employer employee relationship; natural resources; fuels